Faktor-Faktor Yang Berhubungan Dengan Gangguan Fungsi Paru Pada Pekerja Yang Terpapar Potassium Permanganate Dan Phosphoric Acid Di Industri Garmen - Cecep Fathurrahman; Siswi Jayanti; - Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2014)
One of the negative effects of the garment industry was the air pollution by potassium permanganate and phosphoric acid that produced in the pp spray process. Potassium permanganate and phosphoric acid were a chemical irritant which inhaled by the workers will result impaired lung function with early symptoms such as asphyxiate, sore throat, coughing, etc. The purpose of this research was to know the factors (age, working periode, nutritional status, smoking habit, and habits of sport) were associated with impaired lung function in workers exposed to potassium permanganate and phisphoric acid in garment industry. This research was observational research with a cross sectional research design approach. The population of this research was the entire workers of PT Sai Apparel Industries in laundry department in pp spray section amounted to 72 people with a sample of 42 people. Samples were taken by simple random sampling. Data analysis was performed using univariate and bivariate using Chi Square test. The results showed that there was a significant relationship between the independent variables with the dependent variable (impaired  lung function) are working periode (p value = 0.016), smoking (p value = 0.007) , and use of PPE (p value = 0.030) and showed no relationship that age (p value = 0.094), nutritional status (p value = 0.353), and exercise habits (p value = 0.139). It is therefore necessary the use of respirator are strictly monitoring and continuous on the workers and the need to make more effort to lower the levels of potassium permanganate and phosphoric acid in the air with exhaust after work stopped, and make rotation work on workers in the laundry department in pp spray section PT Sai Apparel Industries